Comparative evaluation of acute phase proteins by C-reactive protein (CRP) and serum amyloid A (SAA) in nonhuman primates and feline carnivores - Tohru Kimura (BMC, 2022)
Abstract The feasibility of a commercially available assay for C-reactive protein (CRP, CRP for humans: hCRP, and CRP for dogs: vCRP) and a trial reagent of serum amyloid A (SAA, vSAA for animals) were applied to the measurement of acute phase proteins in zoo animals, particularly in nonhuman primates and feline carnivores was evaluate. Results showed that hCRP and vSAA methods were applicable to measure CRP and SAA in Haplorhini. There was a highly significant correlation between both parameters with remarkably high correlation coefficient. A higher proportion of Bonnet macaques in Haplorhini, and the linear regression with good correlation between hCRP and vSAA levels were observed. Reference values in healthy Bonnet macaques were hCRP (46.86 ± 30.97 nmol/L) and vSAA (9.06 ± 1.95 μg/mL). Although Ring-tailed lemur, which belonging to Strepsirrhini, showed low vSAA concentrations (reference values: 1.08 ± 0.47 μg/mL), vSAA in patients was apparently elevated. The vCRP and vSAA methods were applicable to measurements of CRP and SAA in feline carnivores for highly significant correlation between both parameters. Theses two methods were also been deteded in lions, tigers and cheetahs. vSAA assays can be applied to measure SAA levels in other carnivores and herbivores. In conclusion, vSAA systems have potential utility as diagnostic tools for health screening and prediction in zoo animals.